Surface-phosphorized lithium-rich lithium ferrite as well as preparation method and application thereof

By surface phosphating treatment and doping Zr elements on lithium-rich lithium ferrate, the problem of high residual alkaline substances on the surface is solved, the capacity and cycle stability of the battery are improved, and the service life of the battery is extended.

CN119921007APending Publication Date: 2025-05-02HUBEI WANRUN NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510104223.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The surface of lithium lithium-rich ferrate (Li5FeO4) has high residual alkaline substances, which leads to difficulties in preparing battery pole sheets and battery safety problems.

Method used

By performing surface phosphating of lithium lithium ferrate, a phosphorus layer is formed, the surface residual alkali is converted and eliminated, and Zr elements are doped to increase the diffusion rate of lithium ions.

Benefits of technology

It significantly improves the capacity and cycle stability of lithium lithium ferrate, extends the service life of the battery, and reduces the irreversible loss of lithium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119921007A_ABST
    Figure CN119921007A_ABST
Patent Text Reader

Abstract

The invention provides surface-phosphatized lithium-rich lithium ferrite and a preparation method and application thereof, and belongs to the field of lithium ion batteries, the surface-phosphatized lithium-rich lithium ferrite comprises an inner core and a coating layer coating the surface of the inner core, the inner core is Zr-element-doped lithium-rich lithium ferrite, the coating layer is a phosphorus layer, the chemical formula of the phosphorus layer is Li5FeZrxO4 + 2x (at) (Li3PO4) 2x, and x is larger than or equal to 0.01 and smaller than or equal to 0.1. The lithium-rich lithium ferrite is subjected to surface phosphating treatment, surface residual alkali can be converted and effectively eliminated, the capacity of the lithium-rich lithium ferrite can be remarkably improved, meanwhile, a phosphorus layer formed through phosphating treatment is beneficial to reducing irreversible loss of lithium in the charging and discharging process, and the lithium-rich lithium ferrite can be used for improving the capacity of the lithium-rich lithium ferrite. Therefore, the cycling stability of the prepared secondary battery is improved, and the service life of the secondary battery is prolonged. In addition, the doping of the Zr element enables lithium ions in the lithium-rich lithium ferrite to be separated more easily, so that the specific capacity of the lithium-rich lithium ferrite material in a high compaction state is improved, and the structural stability and the electrochemical performance of the lithium-rich lithium ferrite are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a surface phosphated lithium-rich lithium iron oxide and a preparation method and application thereof. Background Art

[0002] With the growing demand for energy storage, the development of lithium-ion batteries has received increasing attention. In order to increase the energy density of batteries, negative electrode materials such as silicon-oxygen and silicon-carbon are often used. These materials will consume a large amount of active lithium to form a solid electrolyte interface (SEI) during the first charging process, and cause irreversible loss of lithium during the cycle process, thereby reducing the battery capacity. Pre-lithiation technology can effectively solve this problem by providing additional lithium ions during the first charging process. Applying it to the field of new energy vehicles can not only improve the performance of batteries, but also promote the healthy development of the new energy vehicle industry and meet the market's urgent demand for high-performance and high-safety batteries.

[0003] Existing lithium replenishment methods mainly include positive electrode lithium replenishment and negative electrode lithium replenishment. Negative electrode lithium replenishment requires the use of chemically active lithium metal powder, which has extremely high requirements for environmental humidity and is difficult to meet processing conditions. It is also incompatible with existing battery manufacturing processes and poses safety risks. In contrast, positive electrode lithium replenishment is simple to operate, highly safe, and compatible with existing processes, so it has been widely used in the industry.

[0004] As a positive electrode lithium supplement, lithium iron oxide (Li5FeO4) has the advantages of high capacity, low charging voltage platform, low cost and non-toxicity, making it one of the materials with the greatest commercial potential. However, during the preparation process, alkaline substances such as Li2O, LiOH and Li2CO3 are easily left on the surface of Li5FeO4. These alkaline substances react with PVDF during the preparation of the slurry, resulting in gelation of the slurry, which is not conducive to the preparation of battery electrodes. In addition, Li2CO3 releases carbon dioxide gas during the charge and discharge process, which has an adverse effect on the electrolyte and causes battery bulging. Therefore, low residual alkali becomes a key indicator for evaluating battery performance. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a surface phosphated lithium-rich lithium iron oxide and its preparation method and application, aiming to solve the technical problem of high residual alkaline substances on the surface of Li5FeO4.

[0006] In the first aspect, the present invention provides a surface-phosphated lithium iron oxide, comprising a core and a coating layer coated on the surface of the core, wherein the core is lithium iron oxide doped with Zr, and the coating layer is a phosphorus layer, and its chemical formula is Li5FeZr x O 4+2x @(Li3PO4) 2x, where 0.01≤x≤0.1.

[0007] In the technical solution of the embodiment of the present application, by performing surface phosphating treatment on the lithium-rich iron phosphate, the one-step conversion and effective elimination of the residual alkali on the surface are achieved, and the residual alkali is converted into an ion conductor, which significantly improves the capacity of the lithium-rich iron phosphate. At the same time, the phosphorus layer formed by the surface phosphating treatment helps to reduce the irreversible loss of lithium during the charging and discharging process, thereby improving the cycle stability of the secondary battery prepared by the surface phosphated lithium-rich iron phosphate and extending its service life. In addition, the doping of the Zr element can make the lithium ions in the lithium-rich iron phosphate easier to escape, further improving the specific capacity of the lithium-rich iron phosphate material under high compaction, and enhancing the structural stability and electrochemical properties of the lithium-rich iron phosphate.

[0008] In some embodiments, the coating layer has a thickness of 10 to 400 nm.

[0009] In this embodiment, the appropriate thickness of the phosphorus layer can ensure the transmission of lithium ions in the electrode material without affecting its diffusion rate. At the same time, the phosphorus layer can reduce the residual alkaline substances on the surface of the core, avoid slurry gelation, and facilitate the preparation of battery pole pieces.

[0010] In a second aspect, the present application provides a method for preparing the surface-phosphated lithium-rich lithium iron oxide as described in the first aspect, comprising the following steps:

[0011] Mixing the iron source and the lithium source evenly to obtain a first mixed material;

[0012] Performing a first sintering process on the first mixed material to obtain a sintered material;

[0013] adding a phosphorus source and a dispersing grinding aid to the sintering material to obtain a second mixed material;

[0014] Dispersing the second mixed material to obtain composite Li5FeO4;

[0015] The composite Li5FeO4 is subjected to a second sintering treatment to obtain surface phosphated Li5FeO4.

[0016] In the technical solution of the embodiment of the present application, by mixing the iron source and the lithium source and performing the first sintering treatment, a stable lithium-rich lithium iron oxide structure can be formed, and by adding a phosphorus source and a dispersing grinding aid, and dispersing and performing the second sintering treatment, it is helpful to evenly and densely coat the phosphorus layer on the surface of the lithium-rich lithium iron oxide. The electrochemical properties of the lithium-rich lithium iron oxide material can be significantly improved by surface phosphating.

[0017] In some embodiments, the iron source is one or more of Fe2O3, Fe3O4, Fe(OH)3 and Fe2(C2O4)3; and / or the lithium source is one or more of Li2O, LiOH, Li2CO3 and Li2C2O4.

[0018] In this embodiment, different iron sources and lithium sources have different thermal stabilities and reactivity. Selecting appropriate iron sources and lithium sources can optimize the synthesis process, improve the crystallinity and structural stability of the product, improve the synthesis efficiency, and reduce production costs.

[0019] In some embodiments, the molar ratio of Fe in the iron source to Li in the lithium source is 1:(5-5.5).

[0020] In this embodiment, by controlling the molar ratio of Fe and Li, the side reactions that may occur in the synthesis process of the lithium-rich lithium iron oxide material can be reduced, which helps to form a lithium-rich lithium iron oxide material with a good crystal structure and reduce the volume expansion and structural degradation of the lithium-rich lithium iron oxide material during the charge and discharge cycle.

[0021] In some embodiments, the first sintering treatment is high-temperature stepwise sintering, wherein the temperature of the first stage is 500-600° C., and the time is 5-10 hours; the temperature of the second stage is 700-900° C., and the time is 20-30 hours.

[0022] In this embodiment, the first stage sintering helps to initially form the crystal structure of the lithium-rich iron ore, and promotes the volatilization of impurities in the raw materials, thereby improving the purity of the lithium-rich iron ore. The second stage sintering can further promote crystal growth, optimize the arrangement and stacking of crystals, and thus improve the electrochemical properties of the lithium-rich iron ore material. High-temperature stepwise sintering can reduce the defects and stress inside the lithium-rich iron ore material, making the crystal structure more stable, thereby improving the cycle stability and service life of the battery.

[0023] In some embodiments, the phosphorus source is Zr(HPO4)2, and the mass fraction of the phosphorus source is 2-5%; and / or the dispersing and grinding aid is one or more of ethanol, isopropanol, n-butanol and glycerol.

[0024] In this embodiment, Zr(HPO4)2 can effectively provide phosphorus during the sintering process to form a stable phosphorus layer. While consuming the residual alkali on the surface of Li5FeO4, the Zr element is doped into the interior of the Li5FeO4 lattice, reducing the barrier for the movement of Li ions inside Li5FeO4, and significantly improving the specific capacity of Li5FeO4 and the specific capacity under high compaction. Controlling the mass fraction of the phosphorus source at 2-5% can ensure the uniformity and thickness of the phosphorus layer, and avoid the adverse effects of too thick or too thin phosphorus layer on battery performance. Dispersing grinding aids can effectively improve the dispersibility and fluidity of the raw material powder, help to obtain more uniform materials during the mixing and sintering process, and improve the uniform distribution of phosphorus on the surface of lithium iron-rich lithium.

[0025] In some embodiments, the dispersion treatment is carried out by crushing and ball-milling the second mixed material for 2 to 8 hours; and / or the particle size of the composite Li5FeO4 is 1 to 50 μm.

[0026] In this embodiment, the crushing and ball milling process helps to improve the uniformity and dispersibility of the second mixed material, so that the phosphorus source is evenly distributed on the surface of the Li5FeO4 particles, which helps to improve the reaction rate and sintering efficiency in the subsequent sintering process. The particle size of the obtained composite Li5FeO4 is 1 to 50 μm, and the fine and uniform particles help the phosphorus source to be evenly distributed on the surface of the lithium iron-rich lithium ferrate, thereby forming a uniform phosphorus layer during the sintering process.

[0027] In some embodiments, the second sintering treatment is high-temperature stepwise sintering, wherein the temperature of the first stage is 800-1000° C., and the time is 1-3 hours; the temperature of the second stage is 500-700° C., and the time is 5-8 hours.

[0028] In this embodiment, by controlling the sintering temperature in stages, it is helpful to optimize the crystal structure of Li5FeO4, promote the phosphating reaction, improve the uniformity of the phosphating layer, form a stable crystal phase, effectively eliminate the residual alkali on the surface of Li5FeO4 by phosphating, and improve the conductivity of Li5FeO4, thereby improving its capacity. The appropriate temperature and time range can reduce energy consumption and improve production efficiency while ensuring the performance of Li5FeO4.

[0029] In the third aspect, an embodiment of the present application provides a positive electrode plate, including a current collector and an active material layer arranged on at least one side of the current collector, wherein the active material layer includes surface phosphated Li5FeO4 obtained by the preparation method of surface phosphated lithium-rich lithium iron oxide as described in the second aspect; the mass fraction of the surface phosphated Li5FeO4 in the active material layer is 95 to 99 wt%.

[0030] In this embodiment, the positive electrode plate contains the above-mentioned surface phosphated Li5FeO4. Since the surface residual alkalinity value of the lithium-rich lithium iron oxide material is reduced, the specific capacity is improved, which is beneficial to the lithium replenishment effect, and then the positive electrode plate containing it is used in the battery to ensure the overall capacity of the battery.

[0031] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 Schematic diagram of the preparation method of surface phosphated lithium-rich lithium iron oxide in the embodiment of the present application;

[0034] Figure 2 This is a SEM image of the surface phosphated lithium iron oxide rich lithium provided in Example 1 of the present application;

[0035] Figure 3 This is a SEM image of the lithium-rich lithium iron oxide provided in Comparative Example 9 of the present application;

[0036] Figure 4 A comparison of the charging capacity of the lithium-rich lithium iron oxide provided in Example 1 of the present application and Comparative Example 9. DETAILED DESCRIPTION

[0037] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0039] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0040] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0041] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0042] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0043] As a positive electrode lithium supplement, lithium iron oxide has the advantages of high capacity, low charging voltage platform, low cost and non-toxicity, but the alkaline substances such as Li2O, LiOH and Li2CO3 remaining on its surface will cause the slurry to gel and affect the preparation of battery poles. In addition, Li2CO3 in the residual alkali will release carbon dioxide gas during the charging and discharging process, which will not only have an adverse effect on the electrolyte, but also may cause battery bulging, affecting the safety and service life of the battery.

[0044] In order to solve the technical problem of high residual alkaline substances on the surface of lithium-rich iron oxide, the present application provides a surface-phosphated lithium-rich iron oxide and its preparation method and application, wherein a phosphorus layer is introduced on the surface of the lithium-rich iron oxide to achieve the technical effect of reducing the residual alkali content on the surface, and thus the electrochemical performance of the positive electrode sheet containing the surface-phosphated lithium-rich iron oxide is also improved.

[0045] In the first aspect, the present invention provides a surface-phosphated lithium iron oxide, comprising a core and a coating layer coated on the surface of the core, wherein the core is lithium iron oxide doped with Zr, and the coating layer is a phosphorus layer, and its chemical formula is Li5FeZr x O 4+2x @(Li3PO4)2x , where 0.01≤x≤0.1.

[0046] In the technical solution of the embodiment of the present application, the residual alkali on the surface of the lithium-rich lithium iron oxide is consumed by coating the surface with a phosphorus layer, and the risk of slurry gelation is reduced during the preparation of the battery pole piece, thereby improving the preparation quality of the battery pole piece. At the same time, by introducing Zr into the lattice of Li5FeO4, the Zr element can occupy part of the position in the Li5FeO4 lattice. Due to its large ionic radius, the volume change of the lattice during the charge and discharge process can be suppressed, thereby improving the stability of the structure. Understandably, Zr doping can reduce the migration barrier of lithium ions inside Li5FeO4, increase the diffusion rate of lithium ions, and the Li ion diffusion path inside the Li5FeO4 lattice is optimized, reducing the barrier for the movement of Li ions inside Li5FeO4, which helps to improve the specific capacity of the Li5FeO4 material, especially under high compaction density conditions, the specific capacity is significantly improved.

[0047] Furthermore, in some embodiments, the coating layer has a thickness of 10 to 400 nm.

[0048] In the technical solution of the embodiment of the present application, the thickness of the coating layer is controlled within the range of 10 to 400 nm, which can ensure that the residual alkali can be effectively consumed while maintaining good diffusion performance of lithium ions. A coating layer that is too thin cannot effectively inhibit the residual alkaline substances on the surface and the release of gas, while a coating layer that is too thick will increase the internal resistance of the battery and affect the transmission efficiency of lithium ions. Specifically, the thickness of the coating layer can be 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm or any value within the range of 10 to 400 nm.

[0049] In a second aspect, an embodiment of the present application provides a method for preparing a surface-phosphated lithium-rich lithium iron oxide as described in the first aspect, comprising the following steps:

[0050] S1, mixing the iron source and the lithium source evenly to obtain a first mixed material;

[0051] S2, performing a first sintering process on the first mixed material to obtain a sintered material;

[0052] S3, adding a phosphorus source and a dispersing grinding aid to the sintering material to obtain a second mixed material;

[0053] S4, dispersing the second mixed material to obtain composite Li5FeO4;

[0054] S5. The composite Li5FeO4 is subjected to a second sintering treatment to obtain surface phosphated Li5FeO4.

[0055] Among them, Figure 1 As shown, in the present application, the first mixture is obtained by evenly mixing the iron source and the lithium source to ensure that the iron and lithium can be evenly distributed in the subsequent sintering process to form a uniform lithium-rich lithium ferrite structure; thereafter, the first mixture is sintered to obtain a sintered material, and the sintering process can promote the chemical reaction of the iron and lithium sources to form a preliminary structure of lithium-rich lithium ferrite; further, a phosphorus source and a dispersing and grinding aid are added to the sintered material to obtain a second mixture, wherein the phosphorus source is used for the subsequent formation of a phosphorus layer, and the dispersing and grinding aid helps to improve the dispersibility and ball milling efficiency of the mixture; finally, the second mixture is dispersed to obtain a composite Li5FeO4, and the obtained composite Li5FeO4 is subjected to a second sintering treatment. During the second sintering treatment, the phosphorus source reacts with the residual alkali on the surface of the Li5FeO4 material to form a phosphorus layer, i.e., surface phosphated Li5FeO4 is obtained, wherein the dispersion treatment helps to reduce the particle size and increase the specific surface area.

[0056] Further, in some embodiments, the iron source is one or more of Fe2O3, Fe3O4, Fe(OH)3 and Fe2(C2O4)3; and / or, the lithium source is one or more of Li2O, LiOH, Li2CO3 and Li2C2O4.

[0057] In the present application, the selected iron source and lithium source have good thermal stability during high temperature sintering, which is conducive to forming a uniform and stable lithium-rich ferrite structure. At the same time, by reacting a suitable iron source and lithium source, the purity of the product can be improved and the impurity content in the final lithium-rich ferrite material can be reduced.

[0058] Furthermore, in some embodiments, the molar ratio of Fe in the iron source to Li in the lithium source is 1:(5-5.5).

[0059] In the present application, the molar ratio of Fe to Li is in the range of 1:(5 to 5.5), which can ensure that there are enough lithium ions to participate in the electrochemical reaction, thereby improving the specific capacity of the lithium-rich ferrite material. Among them, lithium can promote the formation of a stable crystal structure of the lithium-rich ferrite material, which is beneficial to the deintercalation process of lithium ions and improves the cycle stability. If the lithium content is insufficient, it may cause vacancies in lithium sites in the structure, affecting the cycle performance of the lithium-rich ferrite material; and if the lithium content is too much, it may cause excessive expansion of the lithium-rich ferrite structure, resulting in its structural instability. Specifically, the molar ratio of Fe in the iron source to Li in the lithium source can be 1:5, 1:5.1, 1:5.2, 1:5.3, 1:5.4, 1:5.5 or any value in the range of 1:(5 to 5.5).

[0060] Furthermore, in some embodiments, the first sintering treatment is high-temperature stepwise sintering, wherein the temperature of the first stage is 500-600° C., and the time is 5-10 h; the temperature of the second stage is 700-900° C., and the time is 20-30 h.

[0061] In the present application, the first stage sintering can effectively remove organic matter and adsorbed water in the precursor, which is conducive to initial crystallization and the formation of a preliminary solid structure. Initial crystallization can reduce stress accumulation during sintering at higher temperatures and avoid material rupture. Among them, the sintering temperature of the first stage is 500-600 ° C, and sintering at 500-600 ° C can control the reaction rate and avoid uneven nucleation and growth caused by too fast reaction, thereby obtaining a more uniform microstructure. Further, the second stage sintering is carried out at a high temperature of 700-900 ° C, and the grains grow further to form a microstructure with good crystallinity. Understandably, high temperature helps the material to undergo phase change and form the desired lithium-rich lithium iron phase. At the same time, the second stage sintering can adjust the microstructure of the lithium-rich lithium iron material and optimize the diffusion path of lithium ions. Further, the thermal stability of the lithium-rich lithium iron material can be enhanced by high temperature sintering, and the structural degradation during the subsequent use of the secondary battery can be reduced, thereby improving its cycle stability and service life. In addition, the appropriate sintering time can ensure sufficient reaction between the iron source and the lithium source to form a uniform and stable lithium iron-rich lithium ferrite structure.

[0062] Furthermore, in some embodiments, the phosphorus source is Zr(HPO4)2, and the mass fraction of the phosphorus source is 2-5%; and / or the dispersing and grinding aid is one or more of ethanol, isopropanol, n-butanol and glycerol.

[0063] In the present application, Zr(HPO4)2 is used as a phosphorus source, which can react with the surface of lithium-rich ferrite during the sintering process to form a stable phosphorus layer. In addition, the Zr element can make it easier for Li ions in the lithium-rich ferrite to escape, improve the electrochemical properties of the lithium-rich ferrite, reduce the structural degradation of the electrode material during the charge and discharge process, and increase the specific capacity. Among them, controlling the mass fraction of the phosphorus source at 2-5% can ensure the thickness and integrity of the phosphorus layer. If the phosphorus source is too little, it may not be enough to form a complete phosphorus layer, and too much may cause unnecessary side effects and reduce the energy density of the lithium-rich ferrite material. Specifically, the mass fraction of the phosphorus source can be 2%, 3%, 4%, 5%, or any value within the range of 2-5%.

[0064] In the present application, the added dispersing and grinding aid helps to improve the ball milling efficiency. At the same time, the dispersing and grinding aid will volatilize during the sintering process, so it will not have an adverse effect on the performance of the final product. Specifically, ethanol, isopropanol, n-butanol and glycerol can improve the dispersibility of the powder raw materials, so that the raw materials are more evenly distributed during the mixing and ball milling process, thereby improving the uniformity and consistency of the final product.

[0065] Furthermore, in some embodiments, the dispersion treatment method is: crushing the second mixed material and ball milling for 2 to 8 hours; and / or the particle size of the composite Li5FeO4 is 1 to 50 μm.

[0066] In the present application, the dispersion treatment can reduce the particle size of the second mixture, increase the specific surface area, and help improve its electrochemical activity. In addition, the fine particle size can also shorten the diffusion path of lithium ions, provide more active sites for the embedding and de-embedding of lithium ions, and improve the charge and discharge rate of the lithium-rich ferrite material. Understandably, if the ball milling time is short, it may be difficult to achieve the ideal particle size, and if the ball milling time is too long, the particles may be too fine and even cause agglomeration. Specifically, the particle size of the composite Li5FeO4 obtained after the dispersion treatment is 1 to 50 μm, and the fine particles have a higher specific surface area, which can provide more reaction sites, so that the phosphorus source can be more evenly in contact with the surface of the lithium-rich ferrite, ensuring that the phosphorus source forms a uniform and dense phosphide layer on the surface of the lithium-rich ferrite during the sintering process.

[0067] Furthermore, in some embodiments, the second sintering treatment is high temperature step sintering, the temperature of the first stage is 800-1000° C., and the time is 1-3 hours; the temperature of the second stage is 500-700° C., and the time is 5-8 hours.

[0068] In the present application, the high temperature in the first stage ensures the full progress of the chemical reaction and the formation of the phase, while the low temperature in the second stage contributes to the structural optimization and performance stability of the lithium-rich iron oxide material. Among them, at a temperature of 800 to 1000 ° C, it is conducive to the phosphating reaction. If the temperature is too low, the phosphating reaction may not be complete; if the temperature is too high, it may cause the destruction of the material structure; the sintering time determines the fullness of the phosphating reaction. If the time is too short, the phosphating may not be sufficient; if the time is too long, it may cause the phosphating layer to be too thick or the structure of the lithium-rich iron oxide material to degrade. The low-temperature sintering in the second stage can make the new phase structure formed in the first stage more stable. Low-temperature sintering helps to further homogenize and densify the phosphating layer, improve its stability and electrochemical activity, and the appropriate sintering temperature and time help to improve the thermal stability of the final product, regulate the microstructure of the lithium-rich iron oxide material, avoid unnecessary phase changes and decomposition, and maintain structural stability.

[0069] In the third aspect, an embodiment of the present application provides a positive electrode plate, including a current collector and an active material layer arranged on at least one side of the current collector, the active material layer including surface phosphated Li5FeO4 obtained by the preparation method of surface phosphated lithium-rich lithium ferrate according to the second aspect; the mass fraction of surface phosphated Li5FeO4 in the active material layer is 95 to 99 wt%.

[0070] In the technical solution of the embodiment of the present application, the surface phosphated Li5FeO4 has good structural stability, which helps to maintain the integrity of the electrode structure during the charge and discharge process, thereby extending the service life of the battery. The content of surface phosphated Li5FeO4 in the active material layer is relatively high, which can provide a higher energy density, thereby improving the overall capacity of the battery. Specifically, the mass fraction of surface phosphated Li5FeO4 in the active material layer can be 95wt%, 96wt%, 97wt%, 98wt%, 99wt% or any value in the range of 95 to 99wt%.

[0071] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0072] 1. Preparation method

[0073] Example 1

[0074] This embodiment provides a method for preparing surface phosphated lithium iron-rich lithium oxide. Figure 1 As shown, the following steps are included:

[0075] S1. Fe2O3 and Li2O were weighed according to a molar ratio of Fe: Li of 1:5.2, and Fe2O3 and Li2O were placed in a mixer and stirred at 40 rpm for 5 h until uniformly mixed to obtain a first mixture;

[0076] S2. The first mixture is subjected to a first high-temperature step sintering treatment, the first stage temperature is 550°C, the time is 8h; the second stage temperature is 800°C, the time is 25h, and a sintered material is obtained;

[0077] S3. Adding 3% Zr(HPO4)2 by mass to the sintered material, and adding an appropriate amount of ethanol as a dispersing and grinding aid to obtain a second mixture;

[0078] S4. The second mixture was crushed for 1 h, and then ball-milled for 5 h to uniformly distribute Zr(HPO4)2 on the surface of Li5FeO4 particles to obtain composite Li5FeO4;

[0079] S5. The composite Li5FeO4 is subjected to a second high-temperature stepwise sintering treatment, with the first stage temperature at 900°C for 2 hours and the second stage temperature at 600°C for 6 hours to obtain surface phosphated Li5FeO4, i.e., Li5FeZr 0.02 O 4.08 @(Li3PO4)0.04 .

[0080] Example 2

[0081] This embodiment provides a method for preparing surface phosphated lithium-rich lithium iron oxide, which is different from Example 1 only in that the molar ratio of Fe to Li in Fe2O3 and Li2O is 1:5.0.

[0082] Example 3

[0083] This embodiment provides a method for preparing surface phosphated lithium iron-rich lithium ferrate, which is different from Embodiment 1 only in that the molar ratio of Fe to Li in Fe2O3 and Li2O is 1:5.5.

[0084] Example 4

[0085] This embodiment provides a method for preparing surface phosphated lithium-rich lithium ferrite, which is different from Embodiment 1 only in that the mass fraction of Zr(HPO4)2 is 2%.

[0086] Example 5

[0087] This embodiment provides a method for preparing surface phosphated lithium-rich lithium iron oxide, which is different from Embodiment 1 only in that the mass fraction of Zr(HPO4)2 is 5%.

[0088] Example 6

[0089] This embodiment provides a method for preparing surface phosphated lithium iron-rich lithium oxide, which is different from Example 1 only in that in the second high-temperature step sintering, the first stage temperature is 800°C and the time is 2 hours; the second stage temperature is 500°C and the time is 6 hours.

[0090] Example 7

[0091] This embodiment provides a method for preparing surface phosphated lithium iron-rich lithium oxide, which is different from Example 1 only in that in the second high-temperature step sintering, the first stage temperature is 1000°C and the time is 2 hours; the second stage temperature is 700°C and the time is 6 hours.

[0092] Comparative Example 1

[0093] This comparative example provides a method for preparing surface phosphated lithium-rich lithium iron oxide, which is different from comparative example 1 only in that the molar ratio of Fe to Li in Fe2O3 and Li2O is 1:4.5.

[0094] Comparative Example 2

[0095] This comparative example provides a method for preparing surface phosphated lithium-rich lithium iron oxide, which is different from comparative example 1 only in that the molar ratio of Fe to Li in Fe2O3 and Li2O is 1:6.0.

[0096] Comparative Example 3

[0097] This comparative example provides a method for preparing surface phosphated lithium-rich lithium iron oxide, which is different from Example 1 only in that the mass fraction of Zr(HPO4)2 is 1%.

[0098] Comparative Example 4

[0099] This embodiment provides a method for preparing surface phosphated lithium-rich lithium iron oxide, which is different from Embodiment 1 only in that the mass fraction of Zr(HPO4)2 is 6%.

[0100] Comparative Example 5

[0101] This comparative example provides a method for preparing surface phosphated lithium iron-rich lithium oxide, which is different from Example 1 only in that in the second high-temperature step sintering, the first stage temperature is 600°C and the time is 1 hour; the second stage temperature is 400°C and the time is 4 hours.

[0102] Comparative Example 6

[0103] This comparative example provides a method for preparing surface phosphated lithium iron-rich lithium oxide, which differs from Example 1 only in that, in the second high-temperature step sintering, the first stage temperature is 1200°C, the time is 3 hours; the second stage temperature is 900°C, the time is 10 hours.

[0104] Comparative Example 7

[0105] This comparative example provides a method for preparing surface-phosphated lithium-rich lithium iron oxide, which differs from Example 1 only in that the phosphorus source is ammonium dihydrogen phosphate, and the chemical formula of the surface-phosphated Li5FeO4 obtained is Li5FeO4@(Li3PO4): 0.04 .

[0106] Comparative Example 8

[0107] This comparative example provides a method for preparing surface phosphated lithium iron-rich lithium oxide, which is different from Example 1 only in that ethanol is not added during ball milling.

[0108] Comparative Example 9

[0109] This comparative example provides a method for preparing surface-phosphated lithium-rich lithium iron oxide, which is different from Example 1 only in that no phosphorus source Zr(HPO4)2 is added to obtain secondary sintered Li5FeO4.

[0110] 2. Test Method

[0111] 1. SEM test

[0112] The lithium-rich lithium ferrite prepared in Example 1 and Comparative Example 3 was subjected to SEM detection using a MERLIN Compact field emission scanning electron microscope (model: Quanta200FEG) produced by Zeiss.

[0113] 2. Residual alkali value test

[0114] The residual alkali value of the lithium-rich lithium ferrite prepared in the embodiment and the comparative example was tested by titration method.

[0115] 3. Capacity test

[0116] The lithium iron-rich lithium material prepared in the embodiment and the comparative example was mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a ratio of 8:1:1 to form a slurry, evenly coated on aluminum foil, and evenly compacted under a pressure of 20MPa to form a positive electrode sheet (electrode mixing, coating and other preparation processes are all completed in the air), the negative electrode sheet uses a metal lithium sheet, the electrolyte uses 1 mol / L LiPF6, and the solvent is EC:DMC:EMC=1:1:1 (volume ratio). In a vacuum glove box, the battery shell, positive and negative electrode sheets, diaphragm (PE double-layer ceramic diaphragm), spring sheet, and gasket are assembled into a button battery, and the electrochemical performance test is carried out, and the capacity test is carried out under 3.3-4.3V conditions. The results are shown in Table 1 and Figure 4 shown.

[0117] Table 1 Test results of lithium-rich lithium iron oxide provided in the examples and comparative examples

[0118] project Residual alkali value (%) Specific capacity (mAh / g) Example 1 0.09 686 Example 2 0.08 643 Example 3 0.23 673 Example 4 0.15 681 Example 5 0.07 657 Example 6 0.21 643 Example 7 0.13 646 Comparative Example 1 0.05 537 Comparative Example 2 1.34 671 Comparative Example 3 0.56 666 Comparative Example 4 0.06 613 Comparative Example 5 1.21 654 Comparative Example 6 0.29 597 Comparative Example 7 0.31 634 Comparative Example 8 0.53 637 Comparative Example 9 1.04 534

[0119] III. Analysis of test results of various embodiments and comparative examples

[0120] from Figures 2 to 3 It can be seen that in comparative example 9, no phosphorus source was added, and the surface of the lithium iron oxide rich obtained after secondary sintering was relatively rough and irregular. The surface of the lithium iron oxide rich with surface phosphating prepared in Example 1 was smoother, the particle size was more uniform, and it had a distinct layered structure.

[0121] As can be seen from Table 1, the residual alkali values ​​of the surface phosphated lithium-rich iron oxide prepared in Examples 1-7 are all low, indicating that the preparation method of the present application can effectively reduce the residual alkali value of the surface of lithium-rich iron oxide. At the same time, due to the introduction of the Zr element and the formation of the surface ion conductor, the ionic conductivity of the lithium-rich iron oxide is effectively improved, making it easier for Li ions to escape, and thus under high compaction conditions, its specific capacity is significantly improved. In Comparative Example 1, due to the low Li content, the lithium sites in the structure are vacant, and the specific capacity decreases; in Comparative Example 2, the lithium content is too high, causing the lithium-rich iron oxide structure to expand excessively, resulting in its structural instability and a high residual alkali value; in Comparative Example 3, there is too little Zr(HPO4)2, resulting in insufficient formation of a complete phosphorus layer; in Comparative Example 4, there is too much Zr(HPO4)2, resulting in an uneven and too thick phosphorus layer, reducing the specific capacity of the lithium-rich iron oxide material; in Comparative Example 5, The temperature of the second high-temperature step sintering is too low, the phosphating reaction is incomplete, and the residual alkali value is high; in Comparative Example 6, the second The temperature of high-temperature step-by-step sintering is too high, resulting in the destruction of the structure of the lithium-rich lithium iron oxide material and a decrease in specific capacity; in Comparative Example 7, the phosphorus source is ammonium dihydrogen phosphate, which does not contain the Zr element, so the improvement in specific capacity is small; in Comparative Example 8, ethanol was not added during ball milling, resulting in uneven distribution of raw materials during the mixing and ball milling process, affecting the performance of the final product; in Comparative Example 9, no phosphorus source Zr(HPO4)2 was added, resulting in the inability to effectively eliminate the residual alkali on the surface of the lithium-rich lithium iron oxide, making it difficult for Li ions to escape and reducing the specific capacity.

[0122] from Figure 4 It can be seen that the phosphating-treated lithium-rich iron oxide shows a higher charge capacity at the same voltage, indicating that the phosphating treatment effectively improves the electrochemical properties of the lithium-rich iron oxide material, allowing the lithium-rich iron oxide material to store more electricity without sacrificing voltage. Since the phosphating treatment changes the surface properties of the lithium-rich iron oxide material, improves the ionic conductivity, enhances the insertion / extraction kinetics of Li ions, and optimizes the crystal structure of the lithium-rich iron oxide material, the overall conductivity and capacitance capacity are improved.

[0123] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A surface phosphated lithium iron oxide, characterized in that: The invention comprises a core and a coating layer coated on the surface of the core, wherein the core is lithium iron oxide rich with Zr element, and the coating layer is a phosphorus layer, and its chemical formula is Li5FeZr x O 4+2x @(Li3PO4) 2x , where 0.01≤x≤0.

1.

2. The surface phosphated lithium iron oxide according to claim 1, characterized in that: The coating layer has a thickness of 10 to 400 nm.

3. A method for preparing the surface phosphated lithium-rich lithium iron oxide according to claim 1 or 2, characterized in that: The following steps are involved: Mixing the iron source and the lithium source evenly to obtain a first mixed material; Performing a first sintering process on the first mixed material to obtain a sintered material; adding a phosphorus source and a dispersing grinding aid to the sintering material to obtain a second mixed material; The second mixed material is dispersed to obtain composite Li5FeO4; The composite Li5FeO4 is subjected to a second sintering treatment to obtain surface phosphated Li5FeO4.

4. The method for preparing the surface phosphated lithium iron oxide according to claim 3, characterized in that: The iron source is one or more of Fe2O3, Fe3O4, Fe(OH)3 and Fe2(C2O4)3; and / or, The lithium source is one or more of Li2O, LiOH, Li2CO3 and Li2C2O4.

5. The method for preparing the surface phosphated lithium iron oxide according to claim 4, characterized in that: The molar ratio of Fe in the iron source to Li in the lithium source is 1:(5-5.5).

6. The method for preparing the surface phosphated lithium iron oxide according to claim 3, characterized in that: The first sintering treatment is high-temperature stepwise sintering, with the temperature of the first stage being 500-600° C. and the time being 5-10 hours; the temperature of the second stage being 700-900° C. and the time being 20-30 hours.

7. The method for preparing the surface phosphated lithium iron oxide according to claim 3, characterized in that: The phosphorus source is Zr(HPO4)2, and the mass fraction of the phosphorus source is 2-5%; and / or, The dispersing grinding aid is one or more of ethanol, isopropanol, n-butanol and glycerol.

8. The method for preparing the surface phosphated lithium iron oxide according to claim 3, characterized in that: The dispersion treatment method is: crushing the second mixed material and ball milling for 2 to 8 hours; and / or, The particle size of the composite Li5FeO4 is 1 to 50 μm.

9. The method for preparing the surface phosphated lithium iron oxide rich according to claim 3, characterized in that: The second sintering treatment is high-temperature stepwise sintering, with the temperature of the first stage being 800-1000° C. and the time being 1-3 hours; the temperature of the second stage being 500-700° C. and the time being 5-8 hours.

10. A positive electrode sheet, characterized in that: It comprises a current collector and an active material layer arranged on at least one side of the current collector, wherein the active material layer comprises surface phosphated Li5FeO4 obtained by the preparation method of surface phosphated lithium-rich lithium ferrate as described in any one of claims 3 to 9; the mass fraction of the surface phosphated Li5FeO4 in the active material layer is 95 to 99 wt%.

Citation Information

Cited By

  • Composite coated high-performance lithium-rich lithium ferrite material as well as preparation method and application thereof

    CN120749155A